(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
The current state of the issue is generalized, research objectives are set, a methodology has been developed for assessing the technical condition of operating structures of buildings and structures. An analysis of the existing methods made it possible to establish that there are no methods for calculating building structures brought to practical use, evaluating their technical condition and justifying the possibility of subsequent reliable operation after various influences, as well as under the condition of reconstruction with completion. A procedure is proposed for assessing the technical condition and bearing capacity of exploited structures during reconstruction. A technique has been developed for obtaining the determining parameters of the technical state of structures. It is envisaged that structures and elements throughout the entire life cycle as a result of aging, degradation, and other influences can consistently be in each of the four technical states. The results of the survey and assessment of the technical condition of the building structures of the existing building are presented, on the cover of which it was necessary to mount the canopy. The design, calculations, manufacture and installation of load-bearing steel and enclosing structures of the canopy over the coating of the existing building were carried out in connection with the need to protect the technological equipment and automobiles located on the coating from atmospheric precipitation and other climatic factors. The canopy is a one-story spatial frame, consisting of columns and trusses rigidly connected to reinforced concrete structures, based on the column heads. The connection of trusses with columns is rigid and articulated. The system of ties along the columns and the coating provides the spatial rigidity of the structure. Based on the calculations performed using the FEM PC, the forces in the elements of the computer model were determined, the necessary sections of the elements of the columns, trusses, runs, connections were established. The manufacture, transportation and installation of structures were also performed. From the beginning of work to the commissioning of the facility a little more than 100 days passed.